Clinical predictors of moderate-to-severe pediatric obstructive sleep apnea - Unchiti, Kantarakorn; Samerchua, Artid; Pipanmekaporn, Tanyong; Leurcharusmee, Prangmalee; Sonsuwan, Nuntigar; Phinyo, Phichayut; Patumanond, Jayanton (Frontiers in Pediatrics, 2024)
Background: Children with moderate-to-severe obstructive sleep apnea (OSA) require specific management. However, the risk factors associated with this level of severity in pediatric OSA remain poorly defined. This study aimed to identify clinical predictors of moderate-to-severe pediatric OSA. Methods: This retrospective study enrolled children aged 1 to 18 years who underwent respiratory polygraphy or nocturnal oximetry between January 2013 and December 2017. Patient history, demographics, and sleep study data were analyzed. Logistic regression analysis was conducted to assess risk factors associated with moderate-to-severe pediatric OSA. The STROBE checklist was followed in reporting this research. Results: Among 818 children with a median age of 5 years (IQR: 3, 9), 69.4% were male, and 96.7% were diagnosed with OSA. Of those diagnosed, 542 (66.3%) had moderate-to-severe cases. Independent predictors of moderate-to-severe OSA, with their adjusted odds ratios (95% CI), included: age 1-5 years; 6.16 (3.98 to 9.53), obesity; 2.08 (1.35 to 3.19), adenotonsillar hypertrophy; 1.58 (1.05 to 2.36), frequent snoring (>5 nights/week); 6.86 (4.40 to 10.67), stopped breathing during sleep; 2.34 (1.50 to 3.63), awakening during sleep; 2.04 (1.32 to 3.12), and excessive daytime somnolence; 2.10 (1.28 to 3.43). Conclusion: Children referred to a sleep center demonstrated an increased risk of being diagnosed with moderate-to-severe OSA. Key clinical predictors of moderate-to-severe OSA included age 1-5 years, frequent snoring, episodes of stopped breathing or awakening during sleep, excessive daytime somnolence, obesity, and adenotonsillar hypertrophy. Prioritizing early sleep investigations and appropriate management for children exhibiting these predictors may enhance clinical outcomes and mitigate the risk of long-term complications.